Sistem Rekomendasi Pemilihan Smartphone Android Dengan Dana Terbatas Menggunakan Modified Simple Additive Weighting (M-SAW) - Wicaksono, Adityo Putro (Jurnal Transformatika, 2020)
With the development of communication technology today, the smartphone is one of the choices on communication tools that many users have now. Even now, smartphones have various types and prices that reach user needs, so that with limited funds, they can adjust it to their needs. By creating a smartphone selection recommendation systems, it can make it easier for people in determining smartphone purchases based on available funds, with features, brands, and advantages that are already sophisticated today. The recommendation system is made using a combined method called Modified Simple Additive Weighting (M-SAW), where Simple Additive Weighting (SAW) is used for weighting and normalization process, meanwhile Weighted Product (WP) is used for fixing the weight of criteria, determinating vector S, and ranking process. The result for best recommendation using this method is Oppo F5 Youth with score 0,444. With this recommendation results, makes the user make their decision for smartphone recommendation using this system.